Penerapan Nilai Pendidikan Islam dalam Keluarga Melalui Prophetic Parenting dalam Pembentukan Akhlak Anak Usia Emas di Desa Bukit Barisan - Indrawari, Karliana; Apriadi, Medi; Nurjannah, Nurjannah; Diah, Diah (Belajea: Jurnal Pendidikan Islam, 2021)
The religion of parents in Bukit Barisan is still lacking and parents’ lack of time at home because they are busy working in the garden and lack of control over the children, causing a child to feel free and lack of education from parents. This study aims to determine the problems of parents in the formation of morals in children and to find out how prophetic parenting in the family forms the morals of children in Bukit Barisan Village. This type of research is descriptive analytical, with data collection techniques through observation, interviews, and documentation. While the data analysis techniques include data reduction, data presentation and drawing conclusions. The results of the first study, the problems faced by parents in the formation of morals in children in Bukit Barisan Village are the lack of understanding of parents about religion and lack of supervision from parents. Second, the formation of children’s morals through inculcating the values of Islamic education through prophetic parenting, namely parenting in the form of qudwah hasanah (good examples), al-’adah (habituations), mauidzah hasanah (good advice), uqubah wa kataah (proportionate), and al-’adah. mulahadzah (attention).